Attachment Assessment in treatments, prevention and intervention programs - Silvia Salcuni (Frontiers Research Topics, 2015)
Attachment theory, assessment and research offers a broad, far-reaching view of human functioning, and it can enrich a psychologist's understanding of subjects and their relational adjustment, both in clinical and non-clinical settings. Ongoing research in attachment has led to a number of individual treatments and prevention and intervention programs. The assessment of an individual's attachment organization, can play a crucial role in explaining and previewing the unfolding treatment, the relational adjustments or concerns, and the psychological well-being. We hope to receive empirical papers that give evidence for the usefulness of attachment assessment in both clinical (e.g., patients with Eating Disorder; or Axis-II; psychotherapy patients...) or not clinical population (e.g. Adoptive and/or foster families or couples, Mother-infant assessment in prevention field...). These papers should include methodological issues and information about the participants, the methods used to assess attachment, the process of scorer training and the availability of the manual used to obtain inter-scorer reliability. Case studies may be of interest to the extent that they demonstrate the value of a systematic approach to attachment material. A range of theoretical perspectives is welcome as well presentation of new emergent tools on attachment. Because Frontiers in Psychology is an international journal, each empirical paper should comment on the international implications of the findings and discuss its cross-cultural use. Such comments may include, for example, its linguistic specificity, its robustness in translation, and the cross-cultural generalizability of the constructs and behaviors of the measure and its usual correlates. Cross-cultural generalizability is not, however, a requirement.